Antitumoral and antimetastatic activity of Maitake D-Fraction in triple-negative breast cancer cells - Alonso, Eliana Noelia (2017)
D-Fraction is a proteoglucan extracted from Grifola frondosa (Maitake) mushroom. Previously, we reported that D-Fraction de creases breast cancer (BC) cell viability regardless of hormone receptors and HER2 status of cells. Furthermore, D-Fraction re duces tumor burden and lung metastases in a murine model with hormone-independent LM3 cells. In triple-negative (TNBC) MDA MB-231 cells, we also demonstrated that D-Fraction decreases their migration and invasion capacity. The purpose of the current study is to identify the cellular and molecular mechanisms by which D-Frac tion decreases the migratory/invasive potential of MDA-MB-231 cells. In addition, we propose to evaluate the antitumoral effect of D-Fraction in 4T1 cells, another cell line representative of TNBC subtype. By western blot, we found that D-Fraction increases E-cad herin expression in MDA-MB-231 cells compared to vehicle treat ment (p<0.05). By immunofluorescence, we detected that D-Frac tion decreases the presence of β-catenin in the cytoplasm/nucleus (p<0.001) and promotes its membrane localization (p<0.01). Also, we found that D-Fraction increases the adhesion of MDA-MB-231 cells to substrate (p<0.05). By zymography, we detected that D-Frac tion decreases MMP-2 and MMP-9 activity by 53.59 % (p<0.001) and 27.31 % (p<0.05) respectively, compared to vehicle treatment. On the other hand, manual cell counting and WST-1 assay were performed in TNBC 4T1 cells. D-Fraction decreases the viability of 4T1 cells in a dose- and time-dependent manner (p<0.05). Wound healing assay demonstrated that D-Fraction decreases the migra tory capability of 4T1 cells (p<0.001). By transwell Matrigel assay, D-Fraction reduces the invasive capability of these cells (p<0.001). In conclusion, our results suggest that D-Fraction decreases the via bility and metastatic potential of TNBC cells: promoting an epithelial phenotype; reducing the capability of tumor cells to degrade extra cellular matrix and increasing cell-substrate adhesion.